Tumbuhan Obat Tradisional Suku Dayak Tamambaloh Kabupaten Kapuas Hulu Kalimantan Barat - hilda aqua kusuma wardhani (Universitas Lambung Mangkurat, 2023)
This study aims to identify the types of traditional medicinal plants used by the Tamambaloh Dayak Ethnic, Tamao Village, Embaloh Hulu District, Kapuas Hulu Regency. The research is conducted by survey method, while data is collected by observation, interviews and documentation. The Data obtained was analyzed descriptively and presented in the form of tables and images. The study found that 10 species of traditional medicinal plants used by the Tamambaloh Dayak Ethnic in Tamao Village, Embaloh Hulu District, Kapuas Hulu Regency, namely Eurycoma longifolia Jack (sasapak), Coscinium fenestratum (bararan kunus), Eleutherine palmifolia (bawang lamba’), Zingiber aromaticum (japah bua’), Cymbopogon nardus (L) (sarai dadara’), Saccharum officinarum (L) (tabu dadara’), Blumea balsamifera (L) (ambung-ambung), Pteris longifolia (papaku baruang), Ocimum sanctum (takin sinik), and Abelmoschus manihot (L) (ubi rerear). The organs of plant used as traditional medicine are leaves, stems, roots, flowers and tubers.